Impacto de la violencia intrafamiliar en el desarrollo personal de las usuarias del Departamento de Violencia Intrafamiliar de la Policía Nacional del Cantón Loja, en la actualidad - Cruz Silva, José Luis (2025)
Domestic violence is a social problem that affects many women globally and nationally, has negative effects on family dynamics, and for the direct victims it becomes a factor that limits their personal development. It is a problem characterized by the use of force or any action that causes harm to a member of the family nucleus, usually the woman. The research was guided by the general objective: To analyze the impact that domestic violence has on the personal development of the users of the Department of Domestic Violence of the National Police of Loja Canton, at present, among the specific objectives is; Conceptualize theoretically and methodologically the impact of domestic violence on the users of the Department of Domestic Violence; To determine the causes and effects of the impact of domestic violence on the personal development of the users, to design an intervention proposal from the Social Work approach that contributes to the reduction of the impact of domestic violence on the personal development of the users of the Department of Domestic Violence. The methodology used had a mixed, exploratory and non-experimental approach, using techniques such as the gender violence risk scale, participant observation and focus groups applied to 20 users. The results showed that the users have a moderate level of risk of violence, which affects their personal development due to the personal and psychological limitations it causes. It is concluded that gender violence negatively affects the personal development of the users, since it is a situation that causes physical, emotional and psychological effects that leave women in a state of vulnerability for which they require continuous support to recover